Cell type‐specific gene expression changes in Alzheimer's patients with varying levels of cerebral amyloid angiopathy. (1st February 2022) - Patel, Tulsi; Udine, Evan; Wang, Xue; Allen, Mariet; Is, Ozkan; Tutor‐New, Frederick Q; Carnwath, Troy; Deniz, Kaancan; Lincoln, Sarah J.; Nguyen, Thuy; Malphrus, Kimberly G.; Quicksall, Zachary; et al.
Abstract: Background: Tau neurofibrillary tangles and senile plaques comprised of insoluble amyloid beta are the major histopathological hallmarks of Alzheimer's disease (AD). More than 85% of autopsy‐confirmed AD cases also exhibit some degree of cerebral amyloid angiopathy (CAA), which is characterized by amyloid beta peptide deposits predominantly in blood vessels in the meningeal and intracerebral blood vessels. Consequently, CAA predisposes individuals with AD to cerebral infarction and hemorrhages, accounting for ∼20% of cases in the elderly, which could lead to faster cognitive decline through neurovascular pathway dysfunction. We sought to identify cellular composition changes and characterize cell type‐specific expression associated with CAA pathology in AD patients. Methods: Using 10x Genomics single nuclei RNA sequencing, we profiled nuclei from frozen post‐mortem temporal cortex tissue of 80 individuals with neuropathologic diagnosis of AD and varying levels of CAA, ranging from zero to severe CAA pathology. Braak and Thal measures were also obtained. Downstream analyses were performed in R using Seurat v3.2.3. Quality control filtering based on percentage of genes mapped to the mitochondrial genome and number of genes and UMIs detected resulted in 135, 092 nuclei for analysis. Differential gene expression analyses were performed using R package MAST. Results: We identified 30 clusters which were annotated using established cell type marker genes. There were 3 oligodendrocyte, 14 neuronal (2 excitatory and 3 inhibitory), 5 microglial, 3 endothelial, 4 astrocyte and 1 oligodendrocyte precursor cell cluster. We observed a significant increase in microglial cell proportions with increasing CAA severity, for 3 of the microglial clusters. Conversely, the excitatory neuronal proportion were decreased in individuals with more severe CAA. Further investigation is ongoing to identify the genes underlying the dysregulation of these cell types in CAA. Conclusion: We observed cellular proportion changes for multiple cell types with increasing CAA severity. Additional analyses to determine the effects of CAA independent of AD severity will be performed by adjusting for Braak and Thal measures. Deeper characterization of cell type‐specific expression profiles is expected to provide novel insights into cell‐type specific transcriptome changes associated with vascular risk factors in AD.